2015
DOI: 10.3340/jkns.2015.58.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Flow Alteration for the Treatment of Intracranial Aneurysms That Are Unclippable, Untrappable, and Uncoilable

Abstract: ObjectiveThe treatment of complex intracranial aneurysms remains challenging. One approach is the application of surgical flow alteration to treat aneurysms that are neither clippable, trappable, or coilable. The efficacy and limitations of surgical flow alteration have not yet been established.MethodsCases of complex aneurysms treated with surgical flow alteration (proximal occlusion with or without bypass, distal occlusion with or without bypass and bypass only) were included in this retrospective study.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In our case, proximal and distal occlusion of the ACA at the side of the aneurysm was performed with distal IC-IC bypass. 4) According to Sanai et al, the advantages of IC-IC bypass over EC-IC bypass are as follows: similar diameter of donor-recipient arteries, decreased bypass lengths, and the lack of need to harvest additional donor arteries, reducing surgical durations. 7) These advantages were also evident in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, proximal and distal occlusion of the ACA at the side of the aneurysm was performed with distal IC-IC bypass. 4) According to Sanai et al, the advantages of IC-IC bypass over EC-IC bypass are as follows: similar diameter of donor-recipient arteries, decreased bypass lengths, and the lack of need to harvest additional donor arteries, reducing surgical durations. 7) These advantages were also evident in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Although EC-IC bypass is the more commonly used bypass technique for complex aneurysms, IC-IC bypass can be used as a simpler, less time-consuming technique. In our case, proximal and distal occlusion of the ACA at the side of the aneurysm was performed with distal IC-IC bypass [ 4 ]. According to Sanai et al, the advantages of IC-IC bypass over EC-IC bypass are as follows: similar diameter of donor-recipient arteries, decreased bypass lengths, and the lack of need to harvest additional donor arteries, reducing surgical durations [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these techniques are successful in some cases, the widespread applicability is limited due to stark differences in patient anatomy and the difficult to access posterior location of the vessels. This has led to the increased use of flow diversion in aneurysms deemed unclippable, untrappable, and uncoilable 18 . While flow diversion can lead to some aneurysmal obliteration, some aneurysms remain patent and therefore have a risk of rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of large posterior circulation aneurysms that are unclippable and untrappable, a surgical flow alteration such as distal or proximal trapping of parent artery after EC-IC bypass surgery could be a feasible treatment option. Lee et al [ 8 ] reported favorable treatment outcomes for surgical flow diversion for intracranial aneurysms that were unclippable, untrappable, and uncoilable. They reported a 75% rate of complete obliteration after surgical flow diversion, although the complication rate of surgical flow diversion was 18% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 8 ] reported favorable treatment outcomes for surgical flow diversion for intracranial aneurysms that were unclippable, untrappable, and uncoilable. They reported a 75% rate of complete obliteration after surgical flow diversion, although the complication rate of surgical flow diversion was 18% [ 8 ]. The high morbidity of transcranial surgery remains a great challenge.…”
Section: Discussionmentioning
confidence: 99%